上肢知覚神経伝導検査の基本的問題に関する臨床的検討 - 木村彰男 (リハ医学, 1984)
正常人における, 上肢知覚神経伝導検査を行ない, 以下の結論を得た. 1)橈骨神経, 正中神経および尺骨神経のいずれも, 知覚神経伝導速度は, 順行性刺激でも逆行性刺激でもほぼ一致し, 有意差はなかった. 2)知覚神経活動電位(SNAP)の振幅は, 順行性刺激より逆行性刺激で大きな値が得られるが, 尺骨神経の逆行性刺激では, M波の混入が起こるので注意を要する. 3)橈骨神経と正中神経の間では, SNAPのspread ないし刺激の overflow が生ずるため, 検査に際し充分考慮する必要がある. 同様の現象は, 正中神経と尺骨神経の間でも高頻度に観察される. Sensory nerve conduction studies of the radial, median and ulnar nerves were carried out in healthy normal subjects by conventional techniques using surface electrodes.Sensory nerve conduction velosity (SCV) and the amplutuede of sensory nerve action potential (SNAP) were measured by both the orthodromic and antidromic techniques. Electrodes were placed on the elbow, the wrist and thumb, index and little fingers, respectively. SCV was calculated by the latency time which was taken as the time from stimulus artifact to the first deflection. The amplitude from negative peak to positive peak was considered the amplitude of SNAP.The mean SCV did not show the significant difference between two techniques in the three nerves. On the other hand, the amplitude of SNAP in antidromic measurement was 2 or 3 times higher than that in orthodromic one. But, in the antidromic study of ulnar nerve, M wave overlapped SNAP as the stimulation voltage increased. Consequently, in order to get high amplitude of SNAP, the antidromic technique was preferable, but one had to examine the ulnar nerve carefully because M wave often overlapped.One could also pick up the SNAP from the other nerve at the wrist or elbow, when the digital nerve was stimulated. This phenomenon could be caused by the anatomical abnormality, spread of the SNAP or the overflow of the stimulus current. Therefore, one must carefully perform the sensory nerve conduction study, since this phenomenon was noted between the radial and median nerves and between the median and the ulnar nerves as well.